A 21 Nucleotide Duplication on the α1- and α2-Globin Genes Involves a Variety of Hypochromic Microcytic Anemias, From Mild to Hb H Disease. (June 2015) - Farashi, Samaneh; Faramarzi Garous, Negin; Zeinali, Fatemeh; Vakili, Shadi; Ashki, Mehri; Imanian, Hashem; Najmabadi, Hossein; Azarkeivan, Azita; Tamaddoni, Ahmad
Abstract α-Thalassemia (α-thal) is a common genetic disorder in Iran and many parts of the world. Genetic defects in the α-globin gene cluster can result in α-thal that may develop into a clinical phenotype varying from almost asymptomatic to a lethal hemolytic anemia. Loss of one functional α gene, indicated as heterozygous α+-thal, shows minor hematological abnormalities. Homozygosity for α+- or heterozygosity for α0-thal have more severe hematological abnormalities due to a markedly reduced α chain output. At the molecular level, the absence of three α-globin genes resulting from the compound heterozygous state for α0- and α+-thal, lead to Hb H disease. Here we present a 21 nucleotide (nt) duplication consisting of six amino acids and 3 bp of intronic sequence at the exon-intron boundary, in both the α-globin genes, detected by direct DNA sequencing. This duplication was identified in three patients originating from two different Iranian ethnic groups and one Arab during more than 12 years. The clinical presentation of these individuals varies widely from a mild asymptomatic anemia (heterozygote in α1-globin gene) to a severely anemic state, diagnosed as an Hb H individual requiring blood transfusion (duplication on the α2-globin gene in combination with the – –MED double α-globin gene deletion). The third individual, who was homozygous for this nt duplication on the α1-globin gene, showed severe hypochromic microcytic anemia and splenomegaly. In the last decade, numerous α-globin mutations have demonstrated the necessity of prenatal diagnosis (PND) for α-thal, and this study has contributed another mutation as important enough that needs to be considered.